Unravelling the linkages between conflict and antimicrobial resistance - Aula Abbara; Clare Shortall; Richard Sullivan; Wim Zwijnenburg; Krystel Moussally; Reem Aboshamr; Carine Naim; Angela Uyen; Muhammad H. Zaman; Nabil Karah; Ahmad Kejah; Marwan Osman; et al. (npj Antimicrobials and Resistance)
The compounded impacts of conflicts, natural disasters and climate change increasingly fuel the development and spread of drug-resistant organisms while weakening mitigation efforts through failed governance and health system disruptions. The impacts of conflict drive pathways of exposure to toxic remnants of war and environmental contaminants in settings of forced displacement and broken infrastructure. Tackling antimicrobial resistance in these settings demands context-specific, sustainable interventions that take a transdisciplinary approach.